2015
DOI: 10.32890/uumjls.6.2015.4592
|View full text |Cite
|
Sign up to set email alerts
|

Developing A Model For Pre-Action Dispute Resolution For Strata Dispute Management In Malaysia

Abstract: The Malaysian government has finally announced for the implementation of Strata Management Act 2013 with the aims to cater disputes in the management of strata titled properties. Among the most important aspect of the Act is to introduce Strata Management Tribunal as a platform to resolve disputes among the strata owners and all stakeholders in relation to strata management and maintenance. This research addresses the period prior to the adjudication process by the Tribunal and proposes a model for early dispu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Disputes will inevitably arise in strata living. In Malaysia, the major complaints about strata properties have been mainly reported on the management issues (Mohamad, 2015b). The administration and management issues are the most common types of disputes to arise in strata living.…”
Section: Strata Living and Causes For Strata Disputesmentioning
confidence: 99%
See 3 more Smart Citations
“…Disputes will inevitably arise in strata living. In Malaysia, the major complaints about strata properties have been mainly reported on the management issues (Mohamad, 2015b). The administration and management issues are the most common types of disputes to arise in strata living.…”
Section: Strata Living and Causes For Strata Disputesmentioning
confidence: 99%
“…Apart from the issues relating to financial matters, conflicts usually occur because the strata owners are unaware of the procedures and restrictions before performing renovation works for their units (Fortino, 2017). Based on a study done by Mohamad (2015b), it revealed that the disputes in strata living revolved around several issues such as security, pets, noise, and garbage as well as attitude. Hence, the strata disputes can be categorised into six types of strata disputes, which are financial issues, renovation issues, personal issues, security issues, maintenance issues, and management issues.…”
Section: Strata Living and Causes For Strata Disputesmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, complaints received by the Strata Tribunal Malaysia regarding the lack of collective action totalled 2,642 cases in 2016, increased to 4,964 three years later (Aziz, 2019) and increased again to 5,675 cases the following year (MIEA, 2020). Secondly, Hamzah and Abdullah (2018) collected data from the Housing Tribunal Malaysia, where some 79.8% of the cases received originated from housing managements who filed complaints against parcel holders for failing to discharge their duties of paying the prescribed monthly maintenance fees. From these two cases, the absence of collective action is the main factor for poor maintenance in these housing communities.…”
Section: Introductionmentioning
confidence: 99%